Rift Valley fever: biology and epidemiology - Wright, D; Kortekaas, J; Bowden, TA; Warimwe, GM (Microbiology Society, 2019)
Rift Valley fever (RVF) is a mosquito-borne viral zoonosis that was first discovered in Kenya in 1930 and is now endemic throughout multiple African countries and the Arabian Peninsula. RVF virus primarily infects domestic livestock (sheep, goats, cattle) causing high rates of neonatal mortality and abortion, with human infection resulting in a wide variety of clinical outcomes, ranging from self-limiting febrile illness to life-threatening haemorrhagic diatheses, and miscarriage in pregnant women. Since its discovery, RVF has caused many outbreaks in Africa and the Arabian Peninsula with major impacts on human and animal health. However, options for the control of RVF outbreaks are limited by the lack of licensed human vaccines or therapeutics. For this reason, RVF is prioritized by the World Health Organization for urgent research and development of countermeasures for the prevention and control of future outbreaks. In this review, we highlight the current understanding of RVF, including its epidemiology, pathogenesis, clinical manifestations and status of vaccine development.